Process hierarchy for GSD based user-centric requirements elicitation frameworks - Shah, Asadullah (2020)
Abstract – The user-centric requirements elicitation frameworks facilitate the product users during the requirements elicitation process, which positively contributes in the improvement of whole requirements elicitation process. The applications of user-centric requirements elicitation frameworks in global software development projects have demonstrated the improvements in the quality of requirements elicitation process. This article presents a comprehensive hierarchical structure of internal processes running during the requirements elicitation process in user-centric frameworks in GSD contexts. The article presents a multi-layered hierarchy of different internal processes involved during the whole activity of requirements elicitation. The presented structure will help the software development industry to better optimize and manage the requirements elicitation process for globally distributed software development projects. The presented process hierarchy will also help the software engineers to perform the requirements elicitation process with more rigor and comprehensiveness.